The predictive power of tumor mutational burden in lung cancer immunotherapy response is influenced by patients’ sex - Wang, Shixiang; Zhang, Jing; He, Zaoke; Wu, Kai; Liu, Xue‐Song (International journal of cancer, 2019)
Immunotherapy, represented by immune checkpoint inhibitors (ICI), is transforming the treatment of cancer. However, only a fraction of patients show response to ICI, and there is an unmet need for biomarkers that will identify patients more likely to respond to ICI. Here we report that the ICI response prediction biomarker tumor mutational burden (TMB) shows significant sex differences. TMB's predictive power is significantly better for female than for male lung cancer patients. Receiver operating characteristic curve analysis was performed and the area under the curve (AUC) was reported to evaluate the predictive power of TMB in lung cancer ICI response. Hazard ratios (HR) of TMB‐high vs. TMB‐low patients were compared between male and female patients. Both AUC and HR differences between female and male are significant in all available independent lung cancer datasets. However, the AUC of programmed death ligand 1 (PD‐L1) expression does not show a difference between female and male, suggesting TMB, but not PD‐L1 expression has a better predictive power for female than for male lung cancer patients. Our study suggests significant sex differences in the performance of TMB in ICI response prediction. Future development of ICI biomarker should consider sex differences and special efforts should be paid to improve the performance of ICI predictive biomarkers for male lung cancer patients. What's new? Only a fraction of cancer patients show response to immune checkpoint inhibitors (ICI), and there remains an unmet need for biomarkers to select patients most likely to benefit. Inherent sex differences in immune response could potentially influence the performance of predictive biomarkers. Here, the authors report that the emerging biomarker tumor mutational burden (TMB) shows significant sex differences, with TMB's predictive power being significantly better for female than for male lung cancer patients. Future development of predictive biomarkers for ICI response should consider sex differences, and the performance of biomarkers for male lung cancer patients should also be improved.